Testing the accuracy of the geographical map model using spatial statistical methods: Climatic map as a model - Dr. Ziyad Muhammad Hamid (Genius Journals, 2022)
Testing the model is an important step taken to detect the relationships and correlations between the elements of the phenomenon studied in order to measure the accuracy of the spatial models of the cartographic models. This can be implemented through the use of spatial statistical tools that have the ability to deal with geographical databases (Khair, 2002, p. 340). The geographical outputs of any geographical phenomenon depend on two things: the first is the availability of data recorded within the theoretical and practical studies and their validity and accuracy of recording. The second is the method used in the processing methods, which are chosen according to what is requested from the scholars about the type of phenomenon and the nature of its existence. It was necessary for us to choose the most appropriate methods to complete the technical work and produce the closest results in terms of validity and acceptance
Keywords: Ecological Park; Structure; Construction; Architecture